2003
DOI: 10.3201/eid0912.020566
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila abortusPelvic Inflammatory Disease

Abstract: We report the first documented case of an extragestational infection with Chlamydophila abortus in humans. The pathogen was identified in a patient with severe pelvic inflammatory disease (PID) by sequence analysis of the ompA gene. Our findings raise the possibility that Chlamydiaceae other than Chlamydia trachomatis are involved in PID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
0
24
0
2
Order By: Relevance
“…The patient's history revealed that she had extensive contact with sheep in her youth. Diagnostic pelviscopy revealed diffuse coalescence of both adnexes and edematous swelling of the fallopian tubes [107]. PCR analysis of a liquid aspirate obtained from the Douglas pouch identified C. abortus as the causative agent.…”
Section: Human Diseasementioning
confidence: 97%
See 3 more Smart Citations
“…The patient's history revealed that she had extensive contact with sheep in her youth. Diagnostic pelviscopy revealed diffuse coalescence of both adnexes and edematous swelling of the fallopian tubes [107]. PCR analysis of a liquid aspirate obtained from the Douglas pouch identified C. abortus as the causative agent.…”
Section: Human Diseasementioning
confidence: 97%
“…Infectious elementary bodies of C. abortus are shed in large quantities with the products of abortion and infective aerosols are inhaled by people who are exposed while caring for the animals. There are a number of reports of pregnant women who had severe infections, including spontaneous abortion, stillbirth and septicemia, following exposure to animals infected with C. abortus [102][103][104][105][106][107][108]. Fever up to 41°C and flu-like illness may present as initial symptoms that are accompanied by an elevated C-reactive protein, normal or decreased leukcocyte counts and thrombocytopenia [106,108].…”
Section: Human Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…he animal pathogens Chlamydia psittaci and Chlamydia abortus both possess a significant and well-documented zoonotic potential (3,42,53). At the same time, there are marked differences in host specificity, virulence, tissue tropism, and clinical manifestations of these obligate intracellular bacteria (25).…”
mentioning
confidence: 99%